ANTIMICROBIAL AND FREE RADICAL SCAVENGING ACTIVITIES OF FIVE PALESTINIAN MEDICINAL PLANTS - Qabaha, Khaled I. (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
Extracts from five indigenous Palestinian medicinal plants including Rosmarinus officinalis, Pisidium guajava, Punica granatum peel, grape seeds and Teucrium polium were investigated for antimicrobial and free radical scavenging activities against eight microorganisms, using well diffusion method. The microorganisms included six bacterial isolates (i.e. Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginos, Klebsiella pneumonia, Bacillus subtilis and Micrococcus luteus) and two fungal isolates (i.e. Candida albicans and Aspergillus niger). A standard antioxidant assay was performed on the plant extracts to assess their capability in scavenging 2,2-diphenyl-1-picrylhydrazyl (DPPH). Of the five tested plant extract, only Rosmarinus offcinalis extract contained significant antimicrobial activity against all eight microbial isolates including Pseudomonas aeruginosa. Extracts from other four plants exhibited a variable antimicrobial activity against all microorganisms, except Pseudomonas aeruginosa. Significant antioxidant activity was detected in all plant extracts. However, extracts from Pisidium guajava leaves contained significantly higher antioxidant activity compared to the other extracts tested. The antimicrobial and scavenging activities detected in this in vitro study in extracts from the five Palestinian medicinal plants suggest that further study is needed to identify active compounds to target diseases caused by a wide-spectrum pathogens.